Fannia parafemoralis Araujo & Couri, 1996 e Fannia paraisensis Araujo & Couri, 1996: morfologia das fases jovens, ciclo de vida e aspectos morfológicos dos adultos (Diptera - Fanniidae) - Araujo, Paulo Francisco de (1997)
Morphological and biological aspects of Fannia parafemoralis Araújo & Couri 1996 and Fannia paraisensis Araújo & Couri 1996 are studied. ln the morphological study the immature stages of both species are described and illustrated and the adults are characterized by a diagnosis. The species were rared separately and the evolutive cycle was accompanied, with a diet of sacarose and fish. The biological studied parameters are: preoviposition period; oviposition period; number of ovipositions; eggs number/female; eclodibility, life expectation of male and female; emergency; and quantity of male and female. The periods of development of the different larval instars of each studied species are presented in tables.